Design of ideal invisibility cloak in electronic circuits - Anuhya, Bandi (Nanyang Technological University, 2023)
The concept of invisibility cloaks and cloaking has been around for many years as a fictional idea in books to cinemas. Invisibility cloaks have been a trending research topic over the past few years, invisibility cloak is a tool that makes objects or things inside it invisible to the outer world as if there is nothing present in the place this is called cloaking. If realized, the invisibility cloak has the potential to open various possibilities in various fields be it defense, rescue operations, medicine, or technology itself. For example, in case of any disasters, cloaking could be highly useful for search and rescue operations can be concealed from the outside and the world and, a surgeon could make use of the cloak in surgery to look past an undesired obstacle-blocking the patient’s body. Though the concept of cloaking has been widely researched, realizing an invisibility cloak has been a challenge due to its design complications and scattering effects. It is a trade-off as efforts are made in reducing the design complications by making it simpler, but the cloak suffers from the scattering effect. This project aims in realizing ideal invisibility cloaks, using a transformation invariant approach based on transformation optics (TO) that can smoothly redirect static currents around an object and minimize the scattering as much as possible. In the previous research for an electromagnetic cloaking device, the cloak required optical parameters like inhomogeneous permittivity and anisotropic properties which made the realization difficult in practice. These parameters will no longer be an issue and realizing the cloak can be greatly simplified using epsilon-near-zero (ENZ) properties. Hence doped ENZ media and its properties are made used to realize the invisibility cloak in this project. Overcoming the limitations of previous work Omni directional cloaks have been designed that are bifunctional and can not only be implemented in the electromagnetic field but also in any field. The invisibility cloak is designed using COMSOL Multiphysics and is realized digitally, the designed cloaks are omnidirectional, the bifunctional cloak that can function in presence of a dipole source.